The Effects of Exposure to Hyperinflation on Occupational Choice - Jo\~ao M. P. de Mello; Caio Waisman; Eduardo Zilberman (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2013)
We use data on immigrants who live in the United States to study the effects of exposure to hyperinflation on occupational choice. To do so, we calculate the number of years an individual had lived under hyperinflation before arriving to the US. We find that its marginal effect on the probability of being self-employed instead of wage-earner is 0.87 percentage point. This effect depends on the age individuals had when exposed to hyperinflation. In particular, it is stronger for individuals who experienced hyperinflation at an early age, but it vanishes for those over the age of 40. These results suggest that the macroeconomic environment an individual grows up in permanently affects his economic behavior.
Keywords: E31; J24; J61; 330; hyperinflation; self-employment; immigrants